Mechanism of cell-intrinsic adaptation to Adams-Oliver Syndrome gene DOCK6 disruption highlights ubiquitin-like modifier ISG15 as a regulator of RHO GTPases - Cerikan, Berati; Schiebel, Elmar (Small GTPases, 2017)
DOCK6 is a RAC1/CDC42 guanine nucleotide exchange factor, however, little is known about its function and sub-cellular localization. DOCK6 regulates the balance between RAC1 and RHOA activity during cell adhesion and is important for CDC42-dependent mitotic chromosome alignment. Surprisingly, a cell intrinsic adaptation mechanism compensates for errors in these DOCK6 functions that arise as a consequence of prolonged DOCK6 depletion or complete removal in DOCK6 knockout cells. Down-regulation of the ubiquitin-like modifier ISG15 accounts for this adaptation. Strikingly, although most other DOCK family proteins are deployed on the plasma membrane, here we show that DOCK6 localizes to the endoplasmic reticulum (ER) in dependence of its DHR-1 domain. ER localization of DOCK6 opens up new insights into its functions.